Functional Imaging of Pheochromocytoma with 68Ga-DOTATOC and 68C-HED in a Genetically Defined Rat Model of Multiple Endocrine Neoplasia. (8th June 2011) - Miederer, Matthias; Molatore, Sara; Marinoni, Ilaria; Perren, Aurel; Spitzweg, Christine; Reder, Sybille; Wester, Hans-Jürgen; Buck, Andreas K.; Schwaiger, Markus; Pellegata, Natalia S.
Abstract : Rats affected by the MENX multitumor syndrome develop pheochromocytoma (100%). Pheochromocytomas are uncommon tumors and animal models are scarce, hence the interest in MENX rats to identify and preclinically evaluate novel targeted therapies. A prerequisite for such studies is a sensitive and noninvasive detection of MENXassociated pheochromocytoma. We performed positron emission tomography (PET) to determine whether rat pheochromocytomas are detected by tracers used in clinical practice, such as 68Ga-DOTATOC (somatostatin analogue) or 11 C-Hydroxyephedrine (HED), a norepinephrine analogue. We analyzed four affected and three unaffected rats. The PET scan findings were correlated to histopathology and immunophenotype of the tumors, their proliferative index, and the expression of genes coding for somatostatin receptors or the norepinephrine transporter. We observed that mean 68Ga-DOTATOC standard uptake value (SUV) in adrenals of affected animals was 23.3 ± 3.9, significantly higher than in control rats (15.4 ± 7.9; P = .03 ). The increase in mean tumor-to-liver ratio of 11 C-HED in the MENX-affected animals (1.6 ± 0.5) compared to controls (0.7 ± 0.1) was even more significant (P = .0016 ). In a unique animal model, functional imaging depicting two pathways important in pheochromocytoma biology discriminated affected animals from controls, thus providing the basis for future preclinical work with MENX rats.